PEPTIDES WITH ANTIMICROBIAL ACTIVITY PRODUCED BY ISOLATED NATIVE MICROORGANISMS - CORRALES-GARCÍA, Ligia L.; CIRO G., Gelmy L. (Vitae, 2010)
Like proteins, antimicrobial peptides (AMP) are versatile molecules synthesized by microorganisms using enzymatic pathways with no genetic code instruction. AMP have interesting properties in the food and pharmaceutical industries, like their antimicrobial ability against pathogens. Looking for biomolecules from microorganisms requires hard and time consuming chemical analysis of each microorganism extract. The microorganism isolation method proposed in this research allowed us to find antimicrobial peptides produced by bacteria, through interaction between a charged dye mixed with selective agar and metabolites produced by microorganisms. Twenty soil samples from different zones were isolated in selective media; thirty five strains were purified based on interaction between basic dye and charged molecules from bacteria. Streptomyces sp. y Bacillus sp. both genera were identified. Protein extracts were obtained from the isolated microorganisms cultivated in liquid media; peptides and amino acids were identified by thin layer chromatography and electrophoresis. Those extracts with high protein level were used to evaluate bioautography. Two extracts from 35 showed inhibitory activity against E. coli ATCC 8739 (8 mm halo). Method effectiveness for the isolation and the purifying of microorganisms able to produce charged molecules, of industrial interest is demonstrated.